Individual Fired Brick Domestication in Nigeria - Toyin Emmanuel Akinde (Journal of Visual Art and Design, 2017)
Individual fired brick domestication is not widely practiced; yet the fired brick has played and will continue to play an immense role in the global built environment. Its pivotal task of creating and sustaining architectural structures is ancient and has permeated through to contemporary times courtesy of clay's colossal vitality. Clay exploration and exploitation are perhaps most apparent in fired brick production, particularly in first-world countries with a diverse range of clayware such as bricks and tiles. This development has not been fully maximized in Nigeria as a result of the small number of refractory plants whose total production capacity is beneath the nation's building requirements. This scenario makes fired brick procurement costly and limits its accessibility; consequently, it promotes socio-built inequality among viable fired brick prospectors. In view of the aforementioned, this paper advocates individual fired brick domestication in Nigeria's rural and suburban settlements, providing concise practical details, from materials identification and mould fabrication to brick production. When fully harnessed, this is hoped to create jobs, alleviate the country's fired brick deficit, boost individual economic standing, communal economies and ultimately the national economy. Possibly it could serve as a template in similar settings around the world.